Procedural and follow up results with a new balloon expandable stent in unselected lesions. Issue 3 (1st March 1998) - di Mario, C; Reimers, B; Almagor, Y; Moussa, I; Di Francesco, L; Ferraro, M; Leon, M B; Richter, K; Colombo, A
Abstract : Objective: To assess the clinical and angiographic results of the first clinical application of a new balloon expandable stent, the NIR stent, characterised by high longitudinal flexibility and low profile before expansion, and by high radial support and minimal recoil and shortening after expansion. Design: Single centre survey of unselected lesions in consecutive patients. Setting: Tertiary referral centre. Patients and lesions: 93 stents of various length (9, 16, and 32 mm) were implanted in 64 lesions in 41 patients. Twenty lesions (31%) were longer than 15 mm, and 17 lesions (27%) were located in vessels with a diameter smaller than 2.5 mm. Extreme tortuosity of the proximal vessel was present in 15 lesions (23%). All patients were treated with aspirin and ticlopidine. All lesions were evaluated before and after treatment by quantitative angiography, and in 47 lesions (75%) the stent expansion was also controlled by intracoronary ultrasound. Clinical follow up was available in all patients and angiographic follow up was performed in 53 lesions (84%), at a mean (SD) interval of 5.4 (1.7) months. Results: Deployment of the stent failed in two lesions (3%). Minimum lumen diameter increased from 1.01 (0.54) mm to 2.94 (0.49) mm, and diameter stenosis decreased from 66(15)% to 7(11)%. There was one in-hospital non-Q wave myocardial infarction, one sudden death after 40 days, and 17 target lesion revascularisations (27%). Angiographic restenosis (⩾ 50% diameter stenosis) was documented in 19 lesions (36% of all lesions with angiographic follow up), with an average residual diameter stenosis of 43(21)% and minimum lumen diameter of 1.63 (0.74) mm. Restenosis was more common in vessels with a reference diameter < 2.5 mm (45%) and for lesions longer than 15 mm (46%). Conclusions: The NIR stent could be used successfully in most lesions, achieving optimal angiographic results with very few in-hospital or subacute cardiac events. The angiographic restenosis rate and need for target lesion revascularisation remained high in this unfavourable lesion subset, especially in small vessels and long lesions.